Influenza vaccination coverage among persons seeking outpatient medical care for acute respiratory illness in five states in the United States, 2011–2012 through 2018–2019. Issue 12 (19th March 2021) - Wu, Michael J.; Chung, Jessie R.; Kim, Sara S.; Jackson, Michael L.; Jackson, Lisa A.; Belongia, Edward A.; McLean, Huong Q.; Gaglani, Manjusha; Reis, Michael; Beeram, Madhava; Martin, Emily T.; Monto, Arnold S.; et al.
Highlights: Between 2011 and 2019, influenza vaccination coverage among US outpatients was ~55%. Influenza vaccination coverage was lower than national targets of 70%. Coverage was highest among adults older than 65 years and children aged <5 years. Coverage was lowest among persons aged 13–49 years. Abstract: Background: In the United States (U.S.), annual influenza vaccination has been recommended for all persons aged ≥6 months with the Healthy People 2020 coverage target of 70%. However, vaccination coverage has remained around 42–49% during the past eight influenza seasons. We sought to quantify influenza vaccination coverage and factors associated with vaccination in persons seeking outpatient medical care for an acute respiratory illness (ARI). Methods: We enrolled outpatients aged ≥6 months with ARI from >50 U.S. clinics from 2011 to 2012 through 2018–2019 influenza seasons and tested for influenza with molecular assays. Vaccination status was based on documented receipt of the current season's influenza vaccine. We estimated vaccination coverage among influenza-negative study participants by study site, age, and season, and compared to state-level influenza coverage estimates in the general population based on annual immunization surveys. We used multivariable logistic regression to examine factors independently associated with receipt of influenza vaccines. Results: We enrolled 45, 424 study participants with ARI who tested negative for influenza during the study period. Annual vaccination coverage among influenza-negative ARI patients and the general population in the participating states averaged 55% (range: 47–62%), and 52% (range: 46–54%), respectively. Among enrollees, coverage was highest among adults aged ≥65 years (82%; range, 80–85%) and lowest among adolescents aged 13–17 years (38%; range, 35–41%). Factors significantly associated with non-vaccination included non-White race, no college degree, exposure to cigarette smoke, absence of high-risk conditions, and not receiving prior season influenza vaccine. Conclusions: Influenza vaccination coverage over eight seasons among outpatients with non-influenza respiratory illness was slightly higher than coverage in the general population but 15% lower than national targets. Increased efforts to promote vaccination especially in groups with lower coverage are warranted to attain optimal health benefits of influenza vaccine.